Comparative Analysis of the Proteomic Profile of HaCaT Keratinocytes Using a 1DE Concentrating Gel - Kisrieva, Yu.S.; Samenkova, N.F.; Shkrigunov, T.S.; Larina, O.B.; Rusanov, A.L.; Luzgina, N.G.; Kazieva, L.Sh.; Karuzina, I.I.; Petushkova, N.A. (Biomedical Chemistry: Research and Methods, 2023)
Using tandem mass spectrometry with electrospray ionization, a comparative analysis of HaCaT keratinocyte proteins was carried out before and after exposure of cells to sodium dodecyl sulfate (25 mg/ml) for 48 hours; proteins encoded by human chromosome 18 genes were chosen as the comparison proteins. A total of 2418 proteins were detected in the HaCaT immortalized human keratinocytes, 70% of these proteins were identified by two or more unique peptides. Panoramic mass spectrometry analysis identified 38 proteins encoded by chromosome 18 genes, 27 proteins were common to control HaCaT cells and HaCaT cells exposed to SDS. Using the Metascape database (https://metascape.org), an enrichment analysis of GO terms of the Biological Process category of chromosome 18 gene encoded proteins of HaCaT keratinocytes was performed before and after the SDS exposure. The SDS exposure resulted in a slight enrichment of the GO term "response to stimulus" (GO:0050896) and the related GO term "negative regulation of biological process" (GO:0048519). We found decreased expression levels of membrane proteins encoded by chromosome 18 genes related to cell-cell adhesion (GO:0098609), such as DSC1, DSC3, and DSG1. A decrease in the expression level of desmosomal cadherins is characteristic of malignant neoplasms developing from epithelial tissue cells of various internal organs, mucous membranes, and skin. The method of preparation of HaCaT keratinocyte samples used in this work increased the sensitivity of proteomic analysis of cell culture and made it possible to identify twice as many proteins in one gel strip as compared to the number of proteins (1284) in HaCaT samples subjected to osmotic shock and cleavage by trypsin in solution.